La mediación como método alternativo de la cultura de paz y su incidencia en el respeto de los derechos de las personas. - Briones García, Inés Lorena (2016)
This legal research project entitled "MEDIATION AS AN ALTERNATIVE METHOD CULTURE OF PEACE AND ITS IMPACT ON THE RESPECT OF THE RIGHTS OF INDIVIDUALS" conducting a study of the scope of mediation as an alternative method of dispute resolution in transigible, and in cases where it is possible to reconcile agreements without involving denial of rights issues. The aim is to promote a culture of peace, facing a litigation under an adversarial and adjudicative system that has always characterized us. The themes of the justice system, forced to seek other methods of solution and guaranteed in the Constitution of the Republic, and in other Latin American countries already applied the alternative media as a possibility prior settlement of conflicts, before driving through the courts. For this purpose, a theoretical foundation of mediation in the doctrinal, legal framework and comparative law is made. The field research sectors of the population involved with the object of study, determined the need to propose an amendment to Art. Forty-seven of the Law on Arbitration and Mediation, in order that this alternative method to become the first choice to resolve differences of legal significance, through a quick and likely more just, and in a suitable way to promote a culture of peace, which exceed an old taboos that have done nothing to damage the image of operators justice and that the State is the exclusive provider of the service of justice. Applied research methods were inductive and deductive process by practical application as well as the analytical and synthetic.